THE IMPLEMENTATION OF PROBLEM BASED INSTRUCTION LERANING MODEL TO IMPROVE STUDENT'S LEARNING ACHIEVEMENT IN PHYSICS - Sendi, Stevida (2013)
The facts in the field show that some physics learning process are indeed still not in accordance with the purposes set out in the content standards. Based on the results of a pilot studies in a high school in Bandung, which was done by distributing questionnaires and interviews, it indicates that teaching physics in schools is still centered on the teacher. Thus, the students tend to be passive and their ability in solving the problem is relatively low. This leads to a decline in student's achievement shown by the percentage of their Mastery Minimum Criteria (KKM) which is only obtained by 15 % of all students being observed. In addition, the KKM, which has been set by the school at 75, clearly describes the low achievement of the students in the learning process. An alternative effort to be done is by applying the learning model of Problem Based Instruction in the learning process. This model encourages the students to be directly involved in solving problems related to everyday life by doing some investigations. The method used in this study is quasi-experimental research design which carries out the pretest and posttest group design. The sample taken, 38 people, are the second grade students of SMA Negeri 7 from the second semester, academic years of 2012/2013. The result shows that after applying the learning model of Problem Based Instruction, students' achievement does increase. It is shown by the differences in average score obtained by students before and after the treatment. The average score before the treatments reaches 25.607 %, while the after score is 81.680 %, with the average achieved of normalized gain is 0.75, which is in high criteria. In addition, the percentage of students who achieve the KKM is 84.2 %. Based on this result, it can be concluded that the learning model of Problem Based Instruction is proven to be helpful in improving the students' achievement.